Toward a More Competent Labour Force: A Training Levy Scheme for Canada - Adams, Roy J. (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1980)
A Commission of Inquiry on Educational Leave and Productivity recommended the establishment of a training levy scheme in Canada. In this paper the author discusses why such a scheme is necessary, how it might work, what it might cost, and what it would accomplish.